Hypertension and Cholesterol among Late Adults in Indonesia: A Cross-Sectional Population-Based Survey - Uzma Eliyanti; Ihsan Hanif (Journal of Health Economic and Policy Research (JHEPR), 2023)
The global prevalence of hypertension is relatively high. In 2012, the death rate due to cardiovascular disease reached 17 million per year, with 45% of the contributors being hypertension. In 2015, globally, cholesterol cases accounted for 4.5% of ischemia of heart disease and 2% of strokes. Until 2017 and 2020, cholesterol disease was mainly experienced by adults aged 20 years or more, with a percentage of 10% of the population. Objective: The purpose of this study was to determine the relationship between hypertension and cholesterol. Methodology: The design study used data from the 5th batch of the Indonesia Family Life Survey (IFLS-5) organized by the Rand Corporation. IFLS-5 was conducted in 2014-2015, with 16,204 households and 50,148 individuals interviewed. Stratified random sampling to select respondents from the province to the place of residence. This study used a cross-sectional study design with inclusion and exclusion criteria from a total of 11,062 respondents. Results: Respondents with late-adult criteria in Indonesia were 50.17% women aged 51.98 (± 9.51), 84.04% married, 22.22% high school graduates, 70.14% Javanese, and 59.88% urban residents. The prevalence of cholesterol in late adults in Indonesia was 8.26% (95% CI: 0.08 – 0.09). The prevalence of hypertension in late adulthood in Indonesia was 20.91% (95% CI: 0.20 – 0.22). The results showed that cholesterol (OR = 4.06, 95% CI 3.53 – 4.67, p = <0.001) was statistically significant with hypertension. Conclusion: The prevalence of hypertension and cholesterol among late adults in Indonesia shows that hypertension and cholesterol are statistically significant and there was a relationship between people suffering from hypertension and having potential cholesterol disease.